African Swine Fever and Its Socio-Economic Impacts in Indonesia - Ciputra, Lyvia Angeline; Rahman, Andi Simpurusiang; Nurfadhillah, Besse; Masyita; Toliu, Wudhia Windy; Muslimin, Ihram Kautsar; Apada, Andi Magfira Satya; Rell, Fedri (Universitas Airlangga, 2023)
African Swine Fever Virus (ASF) is a viral disease in pigs that affects the supply of food of animal origin. ASF is caused by a double-stranded DNA virus of the family Asfarviridae and genus Asfivirus, which can be transmitted and causes various bleeding events in the internal organs and is accompanied by a very high mortality rate. This disease is generally characterized by fever, lack of appetite, and bleeding from the skin, back, and legs. Even though this virus is not zoonotic and cannot be transmitted to humans, it is fatal and causes tremendous economic loss. This disease spread throughout Asia in a relatively short time in 2019, and it has even been reported that this disease has entered Indonesia since the end of 2019. The impact of this infection resulted in socioeconomic changes in both rural and urban communities, which could then affect the country's economy at the macro level. Several countries are needed in their efforts to control ASF, one of which is to increase quarantine, limit the traffic of pigs, and reduce the population of sick pigs exposed to the ASF virus.